Pengaruh Penerapan Model Pembelajaran Student Team Achievement Division (STAD) Terhadap Hasil Belajar Fisika: (Eksperimen pada Siswa Kelas XI SMK PGRI 11 Jakarta) - Faizah, Saifi; Supardi , Supardi (Cendikia: Jurnal Pendidikan dan Pengajaran, 2023)
The aim of this research is to analyze the influence of Physics learning outcomes using the Student Team Achievement Division (STAD) learning model and conventional learning models. The hypothesis of this research is "There is an influence of the Student Team Achievement Division (STAD) learning model on physics learning outcomes for class XI students at SMK PGRI 11 Jakarta". The research method used in analyzing Physics learning outcomes is the experimental technique. The population in this study were class XI students at SMK PGRI 11 Jakarta, while the sample taken was 60 students consisting of 30 experimental group students and 30 control group students. The test instrument used is a written test in the form of multiple choice with 20 questions that have passed the data requirements test with a homogeneity test and normality test and have been tried out in non-experimental classes first. After the author analyzed the influence of the Student Team Achievement Division (STAD) learning model on physics learning outcomes using the t-test, the author concluded that physics learning outcomes were higher compared to conventional learning models. This can be seen from the value tcount = 5.03 > ttable = 1.86 with a real level of α = 0.05. The benefit of this research is that it provides information that teaching using the Student Team Achievement Division (STAD) learning model can improve students' physics learning outcomes.